2018
DOI: 10.1016/j.jsv.2018.02.048
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of mode-coupling and falling-friction mechanisms in railway curve squeal through a simplified approach

Abstract: Curve squeal is one of the most annoying types of noise caused by the railway system. It usually occurs when a train or tram is running around tight curves. Although this phenomenon has been studied for many years, the generation mechanism is still the subject of controversy and not fully understood. A negative slope in the friction curve under full sliding has been considered to be the main cause of curve squeal for a long time but more recently mode coupling has been demonstrated to be another possible expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The magnitude of all these effects are dependent upon the exact cornering conditions such as the train configuration, creep law and wheel/rail contact geometries. Recent research has investigated the possibility of mode coupling in these conditions [10]. Other effects on creep behaviour can also be captured by the present model.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…The magnitude of all these effects are dependent upon the exact cornering conditions such as the train configuration, creep law and wheel/rail contact geometries. Recent research has investigated the possibility of mode coupling in these conditions [10]. Other effects on creep behaviour can also be captured by the present model.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…Mode coupling has also been investigated as a mechanism of rail corrugation [9]. However experimental and field evidence of this mechanism in railways is only qualitative at this stage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Brunetti developed a method to predict unstable mode selection by modal absorption index from CEA [20]. Ding developed the assessment of the unstable vibration by mode coupling and nonlinear falling friction mechanism [21]. Oberst also modelled the brake pad contact by pressure-depended material properties of lining [22], and Tison had the integration of ABSTRACT -Squeal noise is generated by an unstable friction-induced vibration in a mechanical structure with friction load.…”
Section: Introductionmentioning
confidence: 99%
“…To consider the influence of the vertical dynamics on friction, the 'mode-coupling dynamic instability' mechanism have been employed in combination with falling-friction theories to predict friction-induced instability [8,[11][12][13] . Chiello , et al [14] concluded that the two types of destabilization caused by the falling-friction mechanism and by the mode-coupling mechanism may be combined in each particular situation of squeal; thus, both mechanisms should be explored [15] .…”
Section: Introduction To Friction-induced Squealmentioning
confidence: 99%